U-Pb zircon age of granitogneiss of the Dai Loc complex and their geological significances - Dung, Nguyen Thi; Hieu, Pham Trung; Minh, Nguyen Trung (Vietnam Journal of Earth Sciences, 2015)
Dai Loc granitoid complex located to the north of Kon Tum massif. It is composed of porphyric biotite granitogneiss, two mica granitogneis, granodiorite gneiss and granite migmatite. Rock forming minerals include mainly K-feldspar, Na rich plagioclase, quartz and biotite.Zircons separated from two granitogneiss samples (DLT 02 and DLT 07) collected in the Dai Loc complex were analyzed for U and Pb isotopic compositions using an LA-ICP-MS to determine the protolith ages of the complex. Data acquired from thirty-nine zircon grains provide concordant ages concentrated at 427-423 Ma (weighted mean), indicating that the protolith age of the granitogneiss (age of primary magma crystallization) is late Silurian.ReferencesA. Carter, D. Roque, C. Bristow, P. Kinny, 2001: Understanding Mesozoic accretion in Southeast Asia: Significance of Triassic thermotectonism (Indosinian orogeny) in Vietnam. Geology, 29(3), 211-214. D.J. Cherniak et al., 1997: Rare - earth diffu-sion in zircon. Chemical Geology, 134, 289-301. F. Corfu, J. M. Hanchar, P.W. Hoskin & P. Kinny, 2003: Atlas of zircon textures. Reviews in mineralogy and geochemistry, 53(1), 469-500. M.H. Dodson, 1973: Closere temperature in cooling geochronological and petrological systems. Contrib. Mineral. Petrol. 40, 259-274. T.M. Harrison, R.L. Armstrong, G.K.C. Clarke, 1978: Thermal models and cooling histories from fission-track, K-Ar, Rb/Sr and U/Pb mineral dates, Northern Coast Pluton Complex British Colombia abstract. In: Short Papers of the Fourth International Conference on Geochronology, Cosmochoronology, Isotope Geology. U.S. Geol. Surv., Open File Rep., 167-170. T.M. Harrison et al., 1979 : Geochronology and thermal history of coast plutonic complex, near Prince Rupert, British Columbia. Can.J. Earth Sce. 16, 400- 410. Phạm Trung Hiếu và nnk, 2009: Tuổi đồng vị U-Pb zircon trong granit phức hệ Yê Yên Sun Tây Bắc Việt Nam và ý nghĩa của nó. Tc. Các Khoa học về Trái Đất, T.31, (1), 23-29. Pham Trung Hieu et al., 2015: Late Permian to Early Triassic crustal evolution of the Kontum massif, central Vietnam: zircon U-Pb ages and geochemical and Nd-Hf isotopic composition of the Hai Van granitoid complex. International Geology Review, inpress. P.D. Kinny et al., 1990: Age constraints on the geological evolution of the Narryer Gneiss Complex, Western Australia: Australia Journal of Earth Sciences, 37, 51-69.. C-Y. Lan et al., 2003: Geochemical and Sr-Nd isotopic constraints from the Kontum massif, Central Vietnam on the crustal evolution of the Indochina block, Precam. Res., 122, 7-27. C. Lepvrier et al., 1997: 40Ar/ 39Ar Indosinian age of NW trending dextral shear zones within the Truong Son belt (Vietnam): Cretaceous to Cenozoic overprinting. Tectonophysics, 283, 105-127. Nguyễn Quang Luật, Phạm Trung Hiếu, Nguyễn Tiến Thành, 2012: Tuổi U-Pb zircon và thành phần đồng vị Hf của gabrodiorit khối A-Bung, vùng Đăk Krông - A Lưới. Tạp chí Địa chất, A329, 19-29. E.A. Nagy, H. Maluski, C. Lepvrier et al., 2001: Geodynamic significance of the Kontum Massif in Central Vietnam: Composite 40Ar/39Ar and U-Pb ages from Paleozoic to Triassic, J. Geol., 109, 755-770. Tran Ngoc Nam, 1998: Thermotectonic events from early Proterozoic to Miocene in the Indochina craton: implication of K-Ar ages in Vietnam. J. Asian Earth Sci., 16, 475-484. Trần Ngọc Nam, 2004: Tuổi đồng vị U-Pb của zircon 436 triệu năm trong phức hệ Sông Re ở địa khối Kon Tum và ý nghĩa của nó, Tạp chí Địa chất, A281, 18-23. Trần Ngọc Nam và nnk, 2004: Biến chất nhiệt độ siêu cao Permi-Trias: Va chạm lục địa ở địa khối Kon Tum? TC Địa chất, A285,1-8. Tạ Trọng Thắng, 1998: Tuổi và đặc điểm biến dạng của đới cắt trượt biến dạng dẻo Đà Nẵng - A Lưới - Khe Sanh. TC Địa chất, A245, 81-89. Đào Đình Thục, Huỳnh Trung, 1995: Địa chất Việt Nam. Tập II. Magma. Cục Địa chất Việt Nam. Hà Nội, 359 tr. Trần Văn Trị, Vũ Khúc (đồng chủ biên), 2009: Địa chất và Tài nguyên Việt Nam. Nxb. Khoa học Tự nhiên và Công nghệ, Hà Nội, 390tr. T. Usuki, C. Y. Lan, T. F. Yui, 2009: Early Paleozoic medium-pressure metamorphism in central Vietnam: evidence from Shirmp U-Pb zircon ages. Geosciences Journal, 13(3): 245-256. I.S. Williams and S.Claesson, 1987: Isotopic evidence for the Precambrian provenance and Caledonian metamorphism of high grade paragneisses from the Seve Nappes, Scandinavian Caledonides: II. Ion microprobe zircon U-Th-Pb: Contribution to Mineralogy and Petrology, 97, 205-217. X. H. Zhou, 2003: My thinking about granite genses of South China. Geological Journal of China Universityies, 9 (4): 556-565 (in Chinese with English abstract). Nguyễn Văn Vượng, Vũ Văn Tích, Hansen Bent. 2004: Áp dụng phương pháp Tims U/Pb xác định tuổi kết tinh của khối Đại Lộc. TC Khoa học về Trái Đất, T.26, (3), 202-207.